2020
DOI: 10.21037/qims.2020.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Association between advanced interatrial block and small vessel diseases in the brain

Abstract: Background: The latest evidence shows the association of atrial cardiopathy with embolic strokes of undetermined source. Advanced interatrial block (aIAB) is an electrophysiological mark of atrial cardiopathy.This study investigated the relationship between aIAB and the burden of silent cerebral small vessel diseases (SVD) on magnetic resonance imaging in the absence of atrial fibrillation (AF) and atrial flutter.Methods: This cross-sectional study included 499 patients with normal left ventricular ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…There is a strong association between silent strokes and age, hypertension, carotid stenosis, chronic kidney disease and metabolic syndrome. Some studies have already reported an association of silent strokes with AF, heart failure, coronary artery disease and even with advanced interatrial block (17,18).…”
mentioning
confidence: 99%
“…There is a strong association between silent strokes and age, hypertension, carotid stenosis, chronic kidney disease and metabolic syndrome. Some studies have already reported an association of silent strokes with AF, heart failure, coronary artery disease and even with advanced interatrial block (17,18).…”
mentioning
confidence: 99%
“…We collected data on basic demographic (age and gender) and vascular risk factors. Hypertension, diabetes mellitus (DM), and hyperlipidemia were defined according to our previous criteria (27). Smoking and alcohol intake were dichotomized as ever or never smoked and ever or never drank alcohol.…”
Section: Demography and Vascular Risk Factorsmentioning
confidence: 99%
“…Brain MRI (3.0 Tesla, TIM Trio; Siemens, Erlangen, Germany) was performed to detect SVD. We rated WMH, lacunes, and EPVS according to our previously published criteria (27). All ratings were performed blind to patients' clinical data.…”
Section: Neuroimaging Examinations Of Svdmentioning
confidence: 99%
See 1 more Smart Citation
“…Recientemente, Wang et al (29) investigaron la relación entre BIA-A y el grado de enfermedad cerebral silente de pequeños vasos (SVD) en la resonancia magnética, en (29) .…”
Section: Relación Entre Síndrome De Bayés Y Lesiones Isquémicas Cerebrales Silentesunclassified